Beyond ConCA: Rethinking causality and construction accidents. (November 2018) - Harvey, Eleanor J.; Waterson, Patrick; Dainty, Andrew R.J.
Abstract: The construction industry takes an orthodox approach to safety: Finding root causes, quantifying risk, and often blaming frontline workers. However, safety has reached a plateau and the limitations of this approach are starting to be acknowledged. A sociotechnical systems approach (as applied in the ConCA model) presents new opportunities to understand accident causation by linking immediate accident circumstances with the distal shaping and originating influences. 32 construction safety managers, consultants, and experts contributed their views regarding the hazards of construction (both human and physical) and the difficulties managing these. The findings provide an insight into the work of construction safety managers and their decision making which is influenced by industry-wide pressures and worker attributes over physical hazards. Construction suffers from a wide range of pressures; a combination of both top-down, from the client, and bottom-up challenges from the workforce it attracts. The original ConCA model has been revised to reflect the findings. By applying systems thinking, the relationships between negative perceptions of workers' risk-taking and these challenges can be crystallised. The results support integrating safety into primary activities to increase engagement, learning legacies to transfer knowledge between projects, multi-disciplinary teams to raise risk awareness, empowerment to combat their feelings of dissatisfaction and disloyalty, and collaboration in risk management to incorporate workers' expertise and ensure they feel valued. Graphical abstract: Image 1 Highlights: The ConCA model is updated with interview data from managers and experts. The relationships between distal and immediate accident causes are interpreted. Managers' decisions are influenced by human factors over physical hazards.